1988
DOI: 10.2134/agronj1988.00021962008000010024x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Moisture, and Soil Texture on DCPA Degradation

Abstract: Turf managers sometimes experience poor or early loss of control oftargeted weeds, even when herbicides are applied at recommended rates. This study was conducted to determine the influence of soil temperature and moisture on the rate of DCPA (dimethyl tetrachloroterephthalate) degradation in soil. The effect of six soil temperatures, three soil moistures, and three soil textures on the degradation of DCPA was measured in the laboratory through HPLC analysis. Soil temperature influenced the rate of DCPA degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Low temperatures are reported to be associated with prolonged residue life (Parker and Doxtader 1983;Choi et al 1988;Newton et al 1990;Johnson et al 1995), yet Schmiel et al (2004) report respiration throughout winters in frozen arctic soils and Meyer et al (2004) have isolated strains of Pseudomonas that grow on a range of cold substrates and also adapt to various carbon sources. While first-order breakdown approximates patterns for many herbicides under warm temperate conditions, verification in very cold soils is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Low temperatures are reported to be associated with prolonged residue life (Parker and Doxtader 1983;Choi et al 1988;Newton et al 1990;Johnson et al 1995), yet Schmiel et al (2004) report respiration throughout winters in frozen arctic soils and Meyer et al (2004) have isolated strains of Pseudomonas that grow on a range of cold substrates and also adapt to various carbon sources. While first-order breakdown approximates patterns for many herbicides under warm temperate conditions, verification in very cold soils is needed.…”
mentioning
confidence: 99%
“…Low temperatures are reported to be associated with prolonged residue life (Parker and Doxtader 1983;Choi et al 1988;Newton et al 1990;Johnson et al 1995), yet Schmiel et al (2004) report respiration throughout winters in frozen arctic soils and Meyer et al (2004) have isolated strains of Pseudomonas that grow on a range of cold substrates and also adapt to various carbon sources. Soil moisture content is reported as influential on both persistence and mobility of residues (Parker and Doxtader 1983;Choi et al 1988). Acid soils are reputed to decrease both mobility of residues and dissipation rates (Johnson et al 1995;Stougaard et al 1990).…”
mentioning
confidence: 99%
“…The biological degradation could be enhanced by promoting the growth or stimulating the activity of fumigant‐degrading microorganisms. The abiotic degradation of fumigants (e.g., CP and 1,3‐D) could be accelerated by increasing the concentration of nucleophiles in soil (Gan et al, 1998; Dungan et al, 2001, 2003) and is affected by soil water content (Helweg, 1987; Choi et al, 1988; Walker et al, 1986; Gan et al, 1999). Accelerated transformation mechanism of CP and MITC was related to addition of compost or manure because more organic matter in soils can develop new microbial population with enhanced degradation capacity for MITC and CP (Ibekwe et al, 2001; Dungan et al, 2003).…”
mentioning
confidence: 99%
“…The largest differences occurred on calm, warm, sunny days when the surface soil temperatures within the crop canopy were 8-16 °C lower than those in the fallow area (Table II). It has been reported that soil microbial activities increase with increasing soil temperatures up to a maximum of 30-35 °C and then activity decreases (Walker, 1978; Abou-Assaf and Coats, 1987; Choi et al, 1988). On warm, sunny days in this experiment, the crop canopy probably kept soil surface temperatures closer to 0 Each temperature is a mean of readings taken on July 13 and July 28,1987 (both warm, sunny days).…”
Section: Resultsmentioning
confidence: 57%
“…This effect was especially noticeable after a rainfall when the soil within the canopy took longer to dry out. Although the effect of moisture on soil microbial activity is complex (Kowalenko et al, 1978;Schoen and Winterlin, 1987), activity is reduced if soil moisture is too low (Walker, 1978;Abou-Assaf and Coats, 1987;Choi et al, 1988). In this experiment, the crop canopy may have contributed to higher microbial activity by preserving critical soil moisture levels at the start of each drying period.…”
Section: Resultsmentioning
confidence: 85%